MARKET REACTIONS TO DIVIDENDS ANNOUNCEMENT: AN EVENT STUDY OF BRIS AND BTPS - Amal, Muhammad Ahsanul; Darmawan; Lamondo (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: A dividend announcement is an information disclosed by a public company regarding the distribution of its corporate profits, whether in the form of dividends or retained earnings to strengthen the company in funding future investments. Dividend announcements might have either a positive or negative effect on the market. Methods: This quantitative research uses the event study method in the data collection period of 20 days, ten days before and ten days after the ex-dividend date. The analysis used is a descriptive statistical test, Shapiro-Wilk normality test, and hypothesis test. Results: The study results indicate that the market reaction is a change in the share price of PT. Bank Syariah Indonesia Tbk (BRIS), there is no significant difference between before and after the ex-dividend date but at PT. National Sharia Pension Savings Bank Tbk (BTPS) changes stock prices before and after the ex-dividend date, and there is a significant difference. Furthermore, for abnormal returns at PT. Bank Syariah Indonesia Tbk (BRIS) and PT. National Sharia Pension Savings Bank Tbk (BTPS) before and after the ex-dividend date, there is no significant difference, as well as the trading volume activity of PT. Bank Syariah Indonesia Tbk (BRIS) and PT. National Sharia Pension Savings Bank Tbk (BTPS) before and after the ex-dividend date, there is no significant difference. Conclusion and suggestion: This is because the dividend policy is not a factor of investor interest in investing in the company but is determined through the earning power of the company's assets